Faire valoir et apprécier : des produits alimentaires aux paysages - Geneviève Teil (Projets de Paysage)
The increasing interest in the research object “landscape” is concomitant with the increase of landscapes and their geographical, agronomical, biological, economical, anthropological and social determinants. As for a number of human creations, their studies underline every day the richness and density of the landscape without knowing if it is the object by itself or if the study makes it richer. Whatever the origin, this enrichment is salutary, but it shouldn’t postpone the capture of the object which can remain imperceptible. To overcome this problem, the research program described in this article, proposes rather than a multidisciplinary approach, an a-disciplinary approach. This research process considers the landscape as a creation, a device whose nature constitutes the challenge itself : a social device if it aims to enhance communication between people, biological if it aims to ensure the biodiversity, esthetical if it is supposed to be beautiful.